CO2 Emissions Embodied in Austrian International Trade - Kurt Kratena; Ina Meyer (FIW - Research Centre International Economics, 2010)
This study quantifies the CO2 emissions embodied in Austrian exports and imports, using a two region-input output approach (Austria and the rest of the world). The approach considers differences in production technologies between Austria and the rest of the world, concerning the CO2 coefficients (per unit of output) and the input-output structure (both are taken from data for EU 27). The CO2 emissions embodied in Austrian imports are considerably higher than CO2 emissions embodied in exports, i.e., CO2 for Austrian demand is leaking to the rest of the world. From 1995 to 2005 this negative balance of CO2 in trade has diminished in absolute terms, from 11 million tons (1995) to 6.4 million tons (2005), as CO2 embodied in exports has grown more rapidly than CO2 embodied in imports, thereby creating a huge potential for future carbon leakage.
Keywords: C67; Q56; 330; trade-embodied CO2 emissions; input-output modelling; carbon leakage